Study More Tomorrow - Todd Pugatch; Elizabeth Schroeder; Nicholas Wilson (Global Labor Organization (GLO), 2022)
We design a commitment contract for college students, "Study More Tomorrow," and conduct a randomized control trial testing a model of its demand. The contract commits students to attend peer tutoring if their midterm grade falls below a prespecified threshold. The contract carries a financial penalty for noncompliance, in contrast to other commitment devices for studying tested in the literature. We find demand for the contract, with take-up of 10% among students randomly assigned a contract offer. Contract demand is not higher among students randomly assigned to a lower contract price, plausibly because a lower contract price also means a lower commitment benefit of the contract. Students with the highest perceived utility for peer tutoring have greater demand for commitment, consistent with our model. Contrary to the model's predictions, we fail to find evidence of increased demand among presentbiased students or among those with higher self-reported tendency to procrastinate. Our results show that college students are willing to pay for study commitment devices. The sources of this demand do not align fully with behavioral theories, however.
Keywords: D91; I21; I23; 330; economics of education; higher education; commitment contracts; randomized control trials